Nomadic Education in Northern Pakistan - Brandon Baughn (UMT Education Review, 2018)
Even in the post Education for All (EFA) era, nomadic groups remain largely absent from educational policy and services. Additionally, there is a severe lack of scholarship in the field of nomadic education, with information on groups in Pakistan completely missing from the current discourse. I conducted a qualitative analysis of interviews of the members of the Bakarwal community. This study provides an examination of fresh data and it also functions as a baseline research for future studies on the Bakarwal nomads in Pakistan. I used a mixed methods approach in this study to better understand the educational goals of nomadic groups and to consider alternative methods of education to achieve these goals. In order to determine the benefits and associated challenges of education as perceived by the Bakarwal community eight interviews in total were conducted; two focus group interviews with recent settlers and one with the old settlers of the transhumant Bakarwal community. Five individual interviews with BMS supervisors were also conducted. The qualitative data was validated against the data of 333 BMS students already conducted by BMS supervisors in 32 literacy centers. The most salient finding is that the Bakarwal do value education as being inherently good for their community while acknowledging challenges associated with access and poverty. The implications of these findings are further discussed in relation to theBakarwal in Pakistan as well as the broader nomadic community.